A preliminary survey of the insect fauna of the Hajar Mountain Range, Oman. Issue 15 (26th April 2019) - Monks, Joseph; Ross, Steven; Geiser, Michael; De Prins, Jurate; Sharaf, Mostafa; Wyatt, Nigel; Al Rijeibi, Shadia; Polaszek, Andrew
ABSTRACT: The Hajar Mountain Range of Northern Oman is an important centre of species endemism, and of biogeographical interest as a crossroads between the Afrotropical and Palaearctic regions. Despite this, the invertebrate fauna of the region is largely unknown, with very little dedicated research or surveys having been undertaken until now. Here we present the invertebrate species collected and identified from five different survey locations within the Hajar Mountains. This preliminary checklist contains 296 records, of which 36 are new records for Oman. Our surveys also discovered two new species of ant: Lepisiota omanensis collected from Jebel Qahwan Reserve and at the base of Jebel Akhdar, and Anochetus annetteae from Hibra Village in the Nakhl Region.